Against all Odds - E-Commerce Success in the Luxury Goods Industry - Sebastian Huber; Oliver Gebien (Marketing Review St.Gallen, 2018)
For many years, it has been debated if at all – and to what extent – high-priced goods in general and luxury brands specifically are suitable for online commerce (e.g. Arrigo, 2014 or Dall'Olmo Riley and Lacroix, 2003). Many distinct characteristics of strategic luxury brand management intuitively contradict the dynamics of e-commerce, with its fully transparent pricing and an affinity for lower-priced items, the focus on immediate order fulfilment, a generally younger and highly technology-savvy consumer audience and democratic interaction between consumers and brands, to name just a few (c.f. Müller-Stewens and Berghaus, 2014).
Keywords: 650